Unusual case of placenta accreta - A Case Report - M Poornima; B A Anupama Marnal; H P Sapna (Apollo Medicine)
Introduction: Placenta accreta is a rare and life-threatening condition. The incidence is increasing with increasing cesarean section rates. Detection and management in early gestational weeks are difficult. Conclusion: Here, we have one such case of 39-year multigravida presented with repeated episodes of bleeding per vagina. Keeping differential diagnosis, we investigated further, and it was managed with total abdominal hysterectomy. The diagnosis was confirmed with a histopathology report as placenta accreta.